2021
DOI: 10.3389/fphar.2020.600953
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/Valsartan Reduces Fibrosis and Alleviates High-Salt Diet-Induced HFpEF in Rats

Abstract: Previous studies have confirmed the clinical efficacy of sacubitril/valsartan (Sac/Val) for the treatment of heart failure with reduced ejection fraction (HFrEF). However, the role of Sac/Val in heart failure with preserved ejection fraction (HFpEF) remains unclear. Sac/Val is a combination therapeutic medicine comprising sacubitril and valsartan that acts as a first angiotensin receptor blocker and neprilysin inhibitor (angiotensin-receptor neprilysin inhibitor (ARNI)). Here, we investigated the role of Sac/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This anti-remodelling nature of ARNI is in agreement with data from other laboratories and large clinical studies. Sacubitril/valsartan prevented myocardial fibrosis and remodelling and improved cardiac function after myocardial infarction in mice [ 28 ] and rats [ 29 , 30 ], and in streptozotocin-induced diabetic hearts in mice [ 31 ]; it reduced cardiomyocyte size in Ang II-induced cardiac hypertrophy in mice [ 32 ], attenuated LV fibrosis and dysfunction in high-salt diet-induced diastolic dysfunction in rats [ 33 ], and reduced BP and prevented stroke in stroke-prone hypertensive rats [ 34 ]. A meta-analysis of clinical studies from 2010 to 2019 revealed that ARNI exerted reverse remodelling in terms of reduced LV size and hypertrophy compared with ACE inhibitors or AT1R blockers in patients with HF with a reduced LV ejection fraction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This anti-remodelling nature of ARNI is in agreement with data from other laboratories and large clinical studies. Sacubitril/valsartan prevented myocardial fibrosis and remodelling and improved cardiac function after myocardial infarction in mice [ 28 ] and rats [ 29 , 30 ], and in streptozotocin-induced diabetic hearts in mice [ 31 ]; it reduced cardiomyocyte size in Ang II-induced cardiac hypertrophy in mice [ 32 ], attenuated LV fibrosis and dysfunction in high-salt diet-induced diastolic dysfunction in rats [ 33 ], and reduced BP and prevented stroke in stroke-prone hypertensive rats [ 34 ]. A meta-analysis of clinical studies from 2010 to 2019 revealed that ARNI exerted reverse remodelling in terms of reduced LV size and hypertrophy compared with ACE inhibitors or AT1R blockers in patients with HF with a reduced LV ejection fraction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the effect of LCZ696 in HFpEF with animal studies is urgently needed. Zhang et al 42 reported that LCZ696 inhibited cardiac fibrosis through the TGF‐β1/Smad3 signalling pathway, thereby effectively alleviating the symptoms of high‐salt diet‐induced HFpEF in rats. Miyoshi et al 43 reported that LCZ696 had more favourable effects on the parameters of LV diastolic function and LV fibrosis in isoproterenol‐treated rats than valsartan alone.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 LCZ696 treatment markedly inhibited TGF-β expression compared to valsartan, with a lower percentage of LV fibrotic area, consistent with previous findings based on other cardiac dysfunction models. 37,38,42 Hence, LCZ696 might exert its antifibrotic and antihypertrophic effects in a TGF-β1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In these models, concurrent oral administration of sacubitril/valsartan (68 mg/kg) with doxorubicin for 6 weeks attenuated MMP activity and highly contractile protein α-smooth muscle actin (α-SMA) expression ( Boutagy et al, 2020 ), while intragastric administration of sacubitril/valsartan (68 mg/kg/day) for 4 weeks mitigated cardiac fibrosis, associated with decreases in types I and III collagen protein and mRNA expressions, as well as MMP-2 protein expression ( Zhang et al, 2021a ). Tissue inhibitor of metalloproteinase-2 (TIMP-2) and Smad7 expression—an inhibitory regulator of TGF-β ( Ma et al, 2018 )—were increased in the rats ( Zhang et al, 2021a ), suggestive of a strong suppressive effect of the drug on myocardial fibrosis production.…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%